2018
DOI: 10.1155/2018/1782719
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Inhibits Voltage-Gated Sodium Channels via α2-Adrenoceptors in Trigeminal Ganglion Neurons

Abstract: Dexmedetomidine, an α2-adrenoceptor agonist, is widely used as a sedative and analgesic agent in a number of clinical applications. However, little is known about the mechanism by which it exerts its analgesic effects on the trigeminal system. Two types of voltage-gated sodium channels, Nav1.7 and Nav1.8, as well as α2-adrenoceptors are expressed in primary sensory neurons of the trigeminal ganglion (TG). Using whole-cell patch-clamp recordings, we investigated the effects of dexmedetomidine on voltage-gated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…39 It has been found that DEX could inhibit voltage-gated sodium channels via a2-adrenoceptors in trigeminal ganglion neurons. 40 It is suggested that DEX activates its receptors and inhibits sodium channels induced by lidocaine, resulting in the reverse of inactivated SIRT1 and leading to inhibition of apoptosis. Further studies are needed to verify the interaction between DEX receptors, lidocaine receptor, and SIRT1/FOXO3a signaling (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…39 It has been found that DEX could inhibit voltage-gated sodium channels via a2-adrenoceptors in trigeminal ganglion neurons. 40 It is suggested that DEX activates its receptors and inhibits sodium channels induced by lidocaine, resulting in the reverse of inactivated SIRT1 and leading to inhibition of apoptosis. Further studies are needed to verify the interaction between DEX receptors, lidocaine receptor, and SIRT1/FOXO3a signaling (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…DRG cells were grown in a Neurobasal medium (with 2% B27 supplement, Invitrogen), at 37 °C, with 5% CO2. DRG neurons were grown for 18 h before use 41 , 42 . Whole-cell current-clamp recordings were performed at room temperature to measure currents with HEKA EPC10 (HEKA).…”
Section: Methodsmentioning
confidence: 99%
“…The extracellular solution contained (in mM): 140 NaCl, 5 KCl, 2 CaCl 2 , 1 MgCl 2 , 10 HEPES, and 10 D-glucose, adjusted to pH 7.3 with NaOH, osmolarity 300-310 mOsm. Voltage-clamp experiments were performed at a holding potential of -60 mV 15 , 41 , 42 .…”
Section: Methodsmentioning
confidence: 99%
“…DRG neurons were grown for 18 hours before use. 22,23 Whole-cell current-clamp recordings were performed at room temperature to measure currents with HEKA EPC10 (HEKA). The patch pipettes were pulled from borosilicate capillaries (Chase Scientific Glass Inc., Rockwood, CA, USA).…”
Section: Whole-cell Patch Clamp Recordings In Cultured Mouse Drg Neuronsmentioning
confidence: 99%
“…Voltage-clamp experiments were performed at a holding potential of -60 mV. 10,22,23 Ca2 + imaging of cultured human DRG neurons.…”
Section: Whole-cell Patch Clamp Recordings In Cultured Mouse Drg Neuronsmentioning
confidence: 99%